Relationship between Serum 25-Hydroxyvitamin D Levels and Cardiovascular Disease Risk among Road Sanitations Workers - Magdalena Wartono; Tjam Diana Samara; Adrianus Kosasih; Dian Mediana (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: Road sanitation workers are frequently exposed to sunlight during outdoor work, which may influence vitamin D status. Although several studies suggest that outdoor workers have a lower risk of vitamin D deficiency than indoor workers, evidence regarding the association between 25-hydroxy vitamin D [25-(OH)D] levels and cardiovascular disease (CVD) risk among sanitation workers remains limited. This study aimed to examine the relationship between serum 25(OH)D levels and CVD risk among road sanitation workers. Methods: This analytical cross-sectional study included 105 road sanitation workers in West Cengkareng District, Jakarta, Indonesia selected using consecutive random. The 10-year cardiovascular risk was calculated using the World Health Organization/International Society of Hypertension (WHO/ISH) risk charts. Serum 25-(OH)D levels were measured from peripheral venous blood samples. Data were analyzed using the chi-Square test and Fisher's exact test, with statistical significance defined as p<0.05.Results: Vitamin D deficiency was observed in 59.05% of participants, whereas 85.7% had low-to-moderate CVD risk. No significant association was found between 25(OH)D levels and CVD risk (p=0.582). However, significant associations were identified between age (p=0.001), body mass index (p=0.003), blood pressure (p=0.037), smoking status (p=0.037) and cardiovascular disease risk.Conclusions: Vitamin D deficiency is not associated with increased CVD risk among road sanitation workers. However, regular monitoring of vitamin D status may support occupational health and overall well-being.